Platelet interactions as therapeutic targets for prevention of atherothrombosis. (May 2009) - Smid, Jan; Braun-Dullaeus, Ruediger; Gawaz, Meinrad; Langer, Harald F
Physiologically, platelets perform important tasks to maintain the homeostasis of the vascular wall and the surrounding environment. In pathologic conditions, however, platelets contribute to the formation of atherosclerotic plaques as well as to atherothrombotic events (i.e., acute myocardial infarction). This review aims to elucidate the role of platelets in atherogenesis and atherothrombosis and to provide an insight into current and future strategies for platelet inhibition.